2021
DOI: 10.21037/qims-19-954
|View full text |Cite
|
Sign up to set email alerts
|

Imaging characteristics of H3 K27M histone-mutant diffuse midline glioma in teenagers and adults

Abstract: Background: To assess anatomical and quantitative diffusion-weighted MR imaging features in a recently classified lethal neoplasm, H3 K27M histone-mutant diffuse midline glioma [World Health Organization (WHO) IV].Methods: Fifteen untreated gliomas in teenagers and adults (median age 19, range, 14-64) with confirmed H3 K27M histone-mutant genotype were analysed at a national referral centre. Morphological characteristics including tumour epicentre(s), T2/FLAIR and Gadolinium enhancement patterns, calcification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
2
16
0
1
Order By: Relevance
“…Additionally, the boundaries of the tumor are ill-defined, and mild peritumoral edema may be notable. These radiological features are consistent with a high-grade glioma (4,11,12). Some scholars summarized that H3 K27M-mutant DMGs occurring in the cervical spinal cord usually showed uniform enhancement (13).…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, the boundaries of the tumor are ill-defined, and mild peritumoral edema may be notable. These radiological features are consistent with a high-grade glioma (4,11,12). Some scholars summarized that H3 K27M-mutant DMGs occurring in the cervical spinal cord usually showed uniform enhancement (13).…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, via correlation with molecular profiling, it is hoped that these and related computational techniques may permit the accurate, image-based, non-invasive phenotyping and predictive genotyping of brain tumours. This would be of particular benefit in guiding therapy in the 'non-operable tumours', such as in certain DMGs (12,13). There are, however, many challenges with these techniques, including problems with external generalisation and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…A radiological evaluation of pediatric non-brainstem HGG within the HERBY trial revealed increased contrast enhancement in H3 K27M mutant tumors, not differentiating between H3.1 and H3.3 subgroups [25]; however, a study on pDMG with and without H3 K27M mutations did not find differences regarding the presence of contrast enhancement and necrotic areas with respect to mutation status [32]. Furthermore, a recent study performed by Thust et al in a relatively small cohort of H3 K27M mutant pediatric and young adult DMG (n = 15) did not find characteristic MR morphologic parameters including diffusivity for this tumor entity; however, a control group of WT tumors was absent [33].…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, a recent study performed by Thust et al. in a relatively small cohort of H3 K27M mutant pediatric and young adult DMG ( n = 15) did not find characteristic MR morphologic parameters including diffusivity for this tumor entity; however, a control group of WT tumors was absent [ 33 ].…”
Section: Discussionmentioning
confidence: 99%